Effects of D-003, a Mixture of Sugarcane Wax Acids, on Platelet Aggregation in Hypercholesterolemic Patients - Arruzazabala, María De Lourdes; Molina, Vivian; Lόpez, Ernesto; Castaño, Gladys; Fernández, Lilia; Carbajal, Daisy; Mas, Rosa; Ferrer, José I.; Mendoza, Sarahi; Ramírez, Yoandri (Arzneimittelforschung, 2008)
Increased platelet aggregation contributes to vascular risk. D-003, a mixture of high molecular weight sugarcane wax acids, has shown antiplatelet effects in experimental models and healthy volunteers. This randomised, double-blinded, placebo-controlled study investigated the effects of titrated doses of D-003 (5-20 mg/d) on platelet aggregation in hypercholesterolemic patients. After a 4-week baseline phase, 56 patients were randomised to D-003 5 mg/d or placebo. The doses were doubled every 15 days if arachidonic acid (AA)-induced platelet aggregation was not inhibited at least by 15%.AA (0.75 and 1.5 mmol/L) and collagen (1 µg/mL)-induced platelet aggregation, laboratory and physical safety indicators were assessed at baseline and every 15 days thereafter, when adverse events (AE) were also reported. No significant change of platelet aggregation was found in the placebo group. After 15, 30 and 45 on therapy, D-003 reduced platelet aggregation induced with both AA 0.75 mmol/L (18.1%, 19.0% and 30.3%, respectively) and AA 1.5 mmol/L (17.0%, 16.3% and 22.5%, respectively), and also collagen-induced platelet aggregation (26.6%, 20.8% and 29.4%) (p < 0.01 at days 15 and 30 versus placebo, p < 0.0001 at study completion). The mean inhibition of platelet aggregation with D-003 at day 15, at which all patients had received the lowest dose, was over 15%. Nineteen out of 28 D-003 randomised patients (67.9%) required dose titration to achieve such goal. At trial completion, the mean estimated dose was 11.6 mg/d. D-003 lowered low-density lipoprotein (22.0%), total cholesterol (14.7%) and raised high-density lipoprotein-cholesterol (10.9%) (p < 0.0001 versus placebo). Six patients (2 placebo, 4 D-003) withdrew from the trial, none due to AE. D-003 did not modify the safety indicators with respect to placebo. Four patients (2 placebo, 2 D-003-treated) reported AE: pruritus and increased blood pressure (2 placebo) and rash and polyphagia (2 D-003). In conclusion, D-003 (5-20 mg/d) given as doses titrated every 15 days (5-20 mg/d) inhibited AA- and collagen-induced platelet aggregation in hypercholesterolemic patients and was well tolerated.
Keywords: Antiplatelet drugs; D-003, effect on platelet aggregation, hypercholesterolemic patients; Platelet aggregation; Sugarcane wax acids